IDENTIFICATION OF PROPOLIS AND HONEY SOURCES POLLEN ANALYSIS OF THE SOUTH OF NORTH CAUCASUS AND THE LOWER VOLGA - ELENA YU. BABAEVA; SVETLANA V. POLEVOVA; BORIS G. ZUGKIEV (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Palynomorphological study of propolis and honey from the regions of the North Caucasus and the Lower Volga Russian Federation and Republic of Abkhazia (RA) has been held. Propolis samples have been obtained in Republic of North Ossetia-Alania (RNO-A), in Volgograd and Saratov regions of Russian Federation and RA at 2010 - 2015 years. Honey samples have been obtained in RNO-A and Republic of Ingushetia (RI) at 2015 year. Microscopy, determination of pollen types (PTs) and counting of pollen grains (PGs) carried out in 3-fold repetition on temporary preparations with a cover glass area of 24 x 24 mm under a light microscope. An analysis of the palynological spectra of propolis and honey samples showed the dominance of pollen from plants of the Asteraceae family. Propolis always contained pollen from several PT, a third of the samples of honey were monofloral. An analysis of the occurrence of PT was carried out. All propolis samples aligned according to the degree of contamination. Samples of honey can differ greatly in the wind-pollinated component.